PENGARUH PERUBAHAN HARGA TERHADAP VOLUME PENJUALAN PADA PEDAGANG SEMBAKO - Syah putri, Zulaika; Oktavia Purba, Chelsea; Mardiani; Syuriani Harahap , Evi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of price changes on sales volume among grocery traders. Price changes are one of the important factors that can influence consumer purchasing decisions and the number of products sold in trading activities. This research uses a quantitative approach with a library research method. The data used are secondary data obtained from various literature sources such as scientific journals, reference books, and previous studies relevant to the research topic. Data collection techniques were carried out through documentation studies by reviewing various scientific articles obtained from the Google Scholar database. The collected data were analyzed using descriptive analysis techniques to identify and interpret the relationship between price changes and sales volume. The results of the study indicate that price changes have a significant effect on sales volume among grocery traders. Price increases tend to reduce consumers’ purchasing power, which results in a decrease in sales volume, while price reductions can increase consumer buying interest, which ultimately leads to higher sales volume. Therefore, grocery traders need to consider appropriate pricing strategies in order to maintain customers and increase sales volume amid market price fluctuations.